Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Role of Interactive Radio Instruction in the COVID-19 Education Response - McBurnie, Chris (Open Development & Education, 2020)
Reading Time: 3 minutes At a time when the COVID-19 pandemic has forced over 1.5 billion students out of school, governments in resource-constrained countries have looked to interactive radio instruction (IRI) to ensure educational continuity. In the past week, we spoke with the Rising Academy Network to consider what an IRI programme could look like and why policymakers have […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

The role of interactive radio instruction in the coronavirus (COVID-19) education response - McBurnie, Chris (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Every week that passes we see the number of classrooms closed due to COVID-19 increase. During these unprecedented times, the Hub’s mission — to increase the use of evidence-based decisions around EdTech — is more important than ever. We must make sure learning goes on. […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Monitoring and evaluating radio in education - McBurnie, Chris (EdTech Hub, 2020)
Keywords: _EdTechHub_Output; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Conseils pour l’introduction de la technologie en classe Liste de sources annotée - Allier-Gagneur, Zoé; Lwamba, Etienne (EdTech Hub, 2020)
Cette liste de sources annotée a pour but d’informer la prise de décisions des acteurs du domaine de l’éducation concernant l’introduction de technologies en classe dans les pays à revenu faible et intermédiaire. Cette liste est une introduction qui expose de façon informelle certains des conseils généraux que prodiguent souvent les experts de l’EdTech Hub.
Keywords: F: Helpdesk response; LP: French; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Using Blended Learning to Support Marginalised Adolescent Girls’ Education: A Review of the Evidence - Allier-Gagneur, Zoé; Chuang, Rachel; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
This topic brief reviews evidence about the use of blended learning to support the education of marginalised adolescent girls in low- and middle- income countries.
Keywords: F: Helpdesk response; H:Blended learning; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

A five-part education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2020)
In March 2020, many countries began to close schools to slow the spread of coronavirus. Education leaders have subsequently launched rapid response programmes, implemented measures to support system recovery and explored long-term reforms. This paper proposes a five-part approach to guide education leaders through this process.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:i; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Is there Learning Continuity during the COVID-19 Pandemic? A Synthesis of the Emerging Evidence - McBurnie, Chris; Adam, Taskeen; Kaye, Tom (Journal of Learning for Development, 2020)
Since the onset of COVID-19, governments have launched technology-supported education interventions to ensure children learn. This paper offers a narrative synthesis of emerging evidence on technology-based education to understand the current experiences of learners, teachers and families. Studies find that few students in low- and middle-income countries have access to technology-supported learning with the most marginalised children appearing to have the least educational opportunities. As such, the education response to COVID-19 could widen existing inequalities.
Keywords: dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No DOI found